DESENTRALISASI FISKAL, POLITIK DINASTI, SISTEM PENGENDALIAN INTERNAL, KINERJA, AKUNTABILITAS PELAPORAN KEUANGAN: BUKTI EMPIRIS DI INDONESIA - Ilham Maulana Saud; Gisti Fairuz Trisha (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2020)
This study aims to analyze the influence of fiscal decentralization, dynastic poltical, and total violation of internal control system on accountability of financial reporting of district/city governments moderated by performance variable at District/City Government in Indonesia in 2013-2015. This study used secondary data obtained through the website of BPK RI, the Ministry of Finance, and the Ministry of Home Affairs. The sample in this study was selected based on the purposive sampling method, so as many as 190 samples were obtained, with details of 95 main samples namely district / city governments that were indicated dynastic politics in Indonesia in 2013-2015 and 95 comparative samples namely district /city governments that were not politically indicated dynasty in Indonesia in 2013-2015. Testing the hypothesis in this study using multiple linear regression with MRA (Moderated Regression Analysis), so there are 2 models in the study. The data collected was analyzed first by testing the classical assumptions, then testing the hypothesis was carried out with the SPSS 26.0 test tool. Based on the results of the study it can be concluded that partially the dependent variable on the central government, dynastic politics, and the number of violations of the internal control system has a significant negative effect on the accountability of local government financial reporting, while the variables of regional independence and financial effectiveness do not affect the financial reporting accountability of local governments. Furthermore, the performance variable is able to moderate the effect of dependence on the central government on the accountability of local government financial reporting, but is unable to moderate the influence of regional independence and dynastic politics on the accountability of local government financial reporting